ROSELLE CALYX ETHANOL EXTRACT STIMULATES ORAL MUCOSAL WOUND HEALING - At, Sarwono; Df, Suniarti (International Journal of Applied Pharmaceutics, 2018)
Objective: This study aim to analyze the effect of the roselle calyx ethanol extract on oral mucosal wound healing. Methods: Male Sprague Dawley rats (3 month, 150 g) were housed under standard temperature conditions (20–22°C). Punch biopsy wounds were inflicted on the inferior labial mucosal membrane of rats. All treatments (normal saline; 0.1% triamcinolone acetonide; and 3.75%, 7.5%, and 15% roselle calyx ethanol extract) were applied 2 times daily. Wounded areas were observed after 8 days of treatment. The specimen of the wounded area was prepared and microscopic slides were analyzed under a light microscope. Results: The histological features of the groups treated with TA and 7.5% roselle calyx ethanol extract showed a similar formation of the epidermis layer and no lymphocytic infiltration of the lamina propria. Conclusion: The application of 7.5% roselle calyx ethanol extract could stimulate oral mucosal wound healing.